Immigration: Community Services - Sonoma State University Library (Sonoma State University)
Deborah Roberts, SSU and Jewish Community Free Clinic, Chris Bell, North Bay Sponsoring Committee, Susan Shaw, North Bay Organizing Project, and Davin Cardenas, Graton Day Labor Center will discuss immigration issues from a grassroots perspective.